Early or Delayed Intervention for Bile Duct Injuries following Laparoscopic Cholecystectomy? A Dilemma Looking for an Answer. (2nd February 2015) - Felekouras, Evangelos; Petrou, Athanasios; Neofytou, Kyriakos; Moris, Demetrios; Dimitrokallis, Nikolaos; Bramis, Konstantinos; Griniatsos, John; Pikoulis, Emmanouil; Diamantis, Theodoros
Abstract : Background . To evaluate the effect of timing of management and intervention on outcomes of bile duct injury. Materials and Methods . We retrospectively analyzed 92 patients between 1991 and 2011. Data concerned patient's demographic characteristics, type of injury (according to Strasberg classification), time to referral, diagnostic procedures, timing of surgical management, and final outcome. The endpoint was the comparison of postoperative morbidity (stricture, recurrent cholangitis, required interventions/dilations, and redo reconstruction) and mortality between early (less than 2 weeks) and late (over 12 weeks) surgical reconstruction. Results . Three patients were treated conservatively, two patients were treated with percutaneous drainage, and 13 patients underwent PTC or ERCP. In total 74 patients were operated on in our unit. 58 of them underwent surgical reconstruction by end-to-side Roux-en-Y hepaticojejunostomy, 11 underwent primary bile duct repair, and the remaining 5 underwent more complex procedures. Of the 56 patients, 34 patients were submitted to early reconstruction, while 22 patients were submitted to late reconstruction. After a median follow-up of 93 months, there were two deaths associated with BDI after LC. Outcomes after early repairs were equal to outcomes after late repairs when performed by specialists. Conclusions . Early repair after BDI results in equal outcomes compared with late repair. BDI patients should be referred to centers of expertise and experience.